"If You Don't Name the Dragon, You Can't Begin to Slay It:" Participatory Action Research to Increase Awareness Around Military-Related Traumatic Brain Injury - Gala True; Ray Facundo; Carlos Urbina; Sawyer Sheldon; J. Duncan Southall; Sarah S. Ono (The University of Alabama, 2022)
Hundreds of thousands of U.S. veterans and their families are significantly affected by traumatic brain injury (TBI), yet policy-makers and the general public often lack knowledge about TBI and other "invisible injuries" related to military service. Veterans may face delayed TBI diagnoses and trouble accessing needed health care, and they and their families may face stigma and misperceptions about TBI that impede successful community reintegration. Researchers in the Department of Veterans Affairs (VA) partnered with 45 veterans with TBI and 26 of their family caregivers on a participatory action research (PAR) study that used photovoice methods to explore and convey experiences of community reintegration after TBI. Interview data and images taken by participants were used to communicate stories, reflections, and insights. This paper reports participants' reflections about (a) how they became aware of TBI-related symptoms and the impact of TBI on their lives and relationships, (b) challenges they have encountered-including misconceptions and stigma-when disclosing TBI and other "invisible injuries" to others, and (c) strategies and resources they draw upon to counter these challenges. The authors conclude by sharing participant-identified recommendations for supporting community reintegration after military service-related TBI. This work demonstrates the power of PAR to engage veterans and family caregivers in generating knowledge to inform the programs, policies, and public discourse that affect their lives. A priority for the dissemination of the study's findings has been to raise awareness about TBI among veterans and military caregivers.